Enhancing Teacher Effectiveness in Bihar Operation : Fiduciary Systems Assessment - World Bank (Washington, DC, 2016)
An integrated fiduciary assessment has been carried out to evaluate the arrangementsrelevant to the Bihar Teachers Education Program to determine whether they provide reasonableassurance that the Program funds will be used for their intended purpose. Based on theassessment and agreement on actions required to strengthen the system, which are reflected inthe DLIs and PAP the overall fiduciary framework for program are considered adequate tosupport program management and to reach the desired results. Similar to other states in India, the GoB has a well-developed budgetary framework that ensures allocation of adequate resources to departments and programs. GoB has not faced significant fund constraint and there is sufficient predictability in availability of resources, albeit fund releases tend to be significantly higher in the last quarter of the financial year; As per standard practice and in order to maintain transparency in GoBs financing, two exclusive budget lines have been allocated to this program segregating between revenue and capital expenditures; a significant proportion of the activities i.e. civil works, ICT procurement and key consultancies, under the program will be undertaken by BSEIDC which operates outside the treasury system and uses commercial banking channels for financial flows and payments. Fiduciary framework in the state and consequently the Program, are guided by several rules and legislation including the Bihar Financial Rules, Treasury Code and Budget Manual, PWD Manual and the Companies Act (2013) in case of BSEIDC.